Individual Patient Data Meta-Analysis of Survival and Psychosomatic Self-Regulation from Published Prospective Controlled Cohort Studies for Long-Term Therapy of Breast Cancer Patients with a Mistletoe Preparation (Iscador). Issue 2 (2010) - Ziegler, R.; Grossarth-Maticek, Ronald
Abstract : Mistletoe preparations such as Iscador are in common use as complementary/anthroposophic medications for many cancer indications, particularly for solid cancers. The efficacy is still discussed controversially. This paper presents an individual patient data meta-analysis of all published prospective matched-pair studies with breast cancer patients concerned with long-term application of a complementary/anthroposophic therapy with the mistletoe preparation Iscador. Six sets of data were available for individual patient meta-analysis of breast cancer patients, matched according to prognostic factors into pairs with and without mistletoe (Iscador) therapy. The main outcome measures were overall survival and psychosomatic self-regulation. Overall survival was almost significant in favor of the Iscador group in the combined data set of the randomized studies: estimate of the hazard ratio with 95% confidence interval 0.59 (0.34, 1.02). Overall survival was highly significant in the combined data set of the non-randomized studies: 0.43 (0.34, 0.56). In the combined analysis of the randomized studies, improvement of psychosomatic self-regulation, as a measure of autonomous coping with the disease, was highly significant in favor of the Iscador group: estimate of the median difference 0.45 (0.15, 0.80), P = 0.0051. The analyzed studies show that therapy with Iscador might prolong overall survival and improve psychosomatic self-regulation of breast cancer patients.